Indonesian Legal Framework Related to Online Game Phenomena: A Criminological Review: Kerangka Hukum Indonesia Terkait Fenomena Game Online: Sebuah Tinjauan Kriminologis - Risardi, Alif Wildan (Universitas Muhammadiyah Sidoarjo, 2022)
The development of online games is part of technological developments. Even so, the development of online games negatively impacts criminal acts and crimes caused by online game addiction. This research seeks to analyze the impact of online games from a criminological perspective as well as efforts to formulate future arrangements to minimize the existence of people who are addicted to online games and commit criminal acts due to addiction to online games. This type of research is normative legal research by prioritizing conceptual and statutory approaches. The study results show that the impact of online game addiction from a legal and criminological perspective can lead to crimes or criminal acts due to online game addiction. The occurrence of the crime or criminal acts caused by online games is also influenced by the surrounding environment, which also seems to justify or at least allow the occurrence of these crimes. Therefore, future regulatory efforts to minimize the impact of online games are to make revisions related to the provisions contained in the Regulation of the Minister of Communication and Informatics No. 11 of 2016 concerning the Clarification of Electronic Interactive Games, especially to emphasize the existence of sanctions and coercive elements so that various provisions in the Regulation can be implemented optimally and need to get a follow-up in the form of public policy.